Diagnosing acute appendicitis in children with neutrophil–lymphocyte ratio: a cross-sectional study - Shalaby, Mohamed Mahmoud; Alawi, Ahmed; Fatani, Bayan Mohammed; Alsaggaf, Ameen; Awad, Mohammed (Frontiers in Pediatrics, 2025)
BackgroundDiagnosing acute appendicitis (AA) in children can be challenging due to atypical symptoms and the difficulty in obtaining a comprehensive history. This study aimed to evaluate the value of the neutrophil-to-lymphocyte ratio (NLR) in diagnosing AA in the pediatric population.MethodsThis retrospective cross-sectional study involved 200 pediatric patients aged between 0 and 14 years of both sexes, who underwent appendectomy for suspected acute appendicitis. Data of patients were retrieved from the hospital's patient administration system database. We categorized patients into three surgical groups: Group 1, appendectomy + normal appendix (n = 32); Group 2, appendectomy + acute appendicitis (AA) (n = 133); and Group 3, appendectomy + perforated appendicitis (n = 35).ResultsWhite blood cell (WBC) count, neutrophil count, and NLR were significantly higher in the acute appendicitis and complicated appendicitis groups than those in the normal appendix group and in the complicated appendicitis group than those in the acute appendicitis group. In multivariate regression, WBC count and NLR were associated with AA (P ≤ 0.001). NLR was associated with complicated appendicitis (P = 0.012). It was also significantly associated with AA and complicated appendicitis at cutoff values >1.7 and >3.5, respectively, with 74% and 68.57% sensitivity and 69% and 56.98% specificity.ConclusionsNLR is a potentially useful adjunctive and cost-effective diagnostic marker for AA and complicated appendicitis in the pediatric population.